S-nitrosothiols and the nitrergic neurotransmitter in the rat gastric fundus: effect of antioxidants and metal chelation - De Man, Joris G (1998)
1. The effects of the antioxidants ascorbic acid and α-tocopherol and of the metal chelator ethylenediaminetetraacetic acid (EDTA) were studied on relaxations in response to S-nitrosothiols, authentic nitric oxide (NO) and nitrergic non-adrenergic non-cholinergic stimulation of the rat gastric fundus. 2. The S-nitrosothiols S-nitrosocysteine (1–100 nM), S-nitrosoglutathione (0.01–3 μM) and S-nitroso-N-acetylpenicillamine (0.01–3 μM) induced concentration-dependent relaxations of the rat gastric fundus muscle strips, which were precontracted with prostaglandin F(2α). The relaxations to all S-nitrosothiols were concentration-dependently enhanced by the antioxidants ascorbic acid (0.1–3 μM) and α-tocopherol (3–30 μM) and inhibited by the metal chelator EDTA (26 μM). 3. Ascorbic acid and α-tocopherol alone did not induce a relaxation of the precontracted rat gastric fundus muscle strip. However, when ascorbic acid (1 μM) or α-tocopherol (1 μM) were injected in the organ bath 1 minute after S-nitrosoglutathione (0.1 μM) or after S-nitroso-N-acetylpenicillamine (0.1 μM), they induced an immediate, sharp and transient relaxation. This relaxation was inhibited by the superoxide generator pyrogallol (2 μM). Such a relaxation to ascorbic acid or α-tocopherol was not observed in the presence of S-nitrosocysteine (10 nM). 4. Electrical field stimulation (0.5–4 Hz) of the precontracted rat gastric fundus strips induced frequency-dependent nitrergic relaxations which were mimicked by authentic NO (3–300 nM) and by acidified sodium nitrite NaNO(2) (0.3–10 μM). Ascorbic acid (0.3–3 μM), α-tocopherol (3–30 μM) or EDTA (26 μM) did not affect the relaxations to nitrergic stimulation, NO or NaNO(2). 5. In summary, relaxations to S-nitrosothiols in the rat gastric fundus are enhanced by the antioxidants ascorbic acid and α-tocopherol and inhibited by the metal chelator EDTA. However, relaxations to nitrergic stimulation of the rat gastric fundus or those to authentic NO were not affected by the antioxidants or by the metal chelator. These results indicate that antioxidants and metal chelators have a different effect on the biological activity of S-nitrosothiols and on that of the nitrergic neurotransmitter. Therefore, our results suggest that S-nitrosothiols do not act as intermediate compounds in nitrergic neurotransmission in the rat gastric fundus.